Tinea capitis treatment and management - Alzahrani, Ali; Alshafie, Ali; Murayr, Faisal; Alkhaldi, Mushari; Ghazwani, Mousa; Shamlan, Nareman; Bakri, Sultan; Almugbel, Saad; Alqadheb, Ahmad; Albelihshi, Sharaf (International Journal Of Community Medicine And Public Health, 2018)
Griseofulvin has been the normal treatment for tinea capitis. However, newer antifungal agents, mainly terbinafine, are increasingly being used due to the short period of treatment and more reliable absorption rates. We pursued to compare the efficacy of oral terbinafine and oral griseofulvin in the treatment and management of tinea capitis. A systematic search of PubMed and the Cochrane Library was conducted up to July 2017 to recognize relevant trials. We also searched for additional trials included in published systematic reviews and bibliographies of all relevant studies comparing terbinafine and griseofulvin in the treatment and management of tinea capitis in immunocompetent patients. Five studies comprising 2035 subjects were included. There was no significant difference in efficacy between griseofulvin (mean duration of treatment 8 weeks, range 6-12 weeks) and terbinafine (mean duration of treatment 4 weeks, range 2-6 weeks); odds ratio=1.2 favoring terbinafine (95% confidence interval [CI]=0.79-1.9; p=0.4). Subgroup analysis revealed that terbinafine was more efficacious than griseofulvin in treating Trichophyton species (1.7; 95% CI=1.28-2.1; p<0.001) and griseofulvin was more efficacious than terbinafine in treating Microsporum species (0.4; 95% CI=0.3-0.7; p<0.001). Both griseofulvin and terbinafine demonstrated good safety profiles in the studies. The present meta-analysis recommends that terbinafine is more efficacious than griseofulvin in treating tinea capitis caused by Trichophyton species, while griseofulvin is more efficacious than terbinafine in treating tinea capitis caused by Microsporum species.